2009
DOI: 10.1211/jpp/61.04.0017
|View full text |Cite
|
Sign up to set email alerts
|

Reichardt's dye and its reactions with the alkylating agents 4-chloro-1-butanol, ethyl methanesulfonate, 1-bromobutane and Fast Red B - a potentially useful reagent for the detection of genotoxic impurities in pharmaceuticals

Abstract: Using standard solutions and in the presence of a drug matrix, Reichardt's dye shows promise as a reagent for detection of low levels of industrially important alkylating agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…561 Corrigan et al used betaine 1 as a reagent for the detection of low levels of alkylating agents, such as 4-chloro-1-butanol and ethylmethanesulfonate. 562 The development of assays for the visual detection and quantification of alkylating agents is important because these compounds are potentially genotoxic impurities that may be present in pharmaceuticals. The rationale here is based on the fact that the alkylation of 1 occurs on the phenolate moiety, and the ether generated is colorless, as shown previously by Linert et al 563 in a kinetic study of the methylation of a series of pyridinium-N-phenolate betaine dyes in organic solvents.…”
Section: Chromogenic Chemosensors For Neutral Analytesmentioning
confidence: 99%
“…561 Corrigan et al used betaine 1 as a reagent for the detection of low levels of alkylating agents, such as 4-chloro-1-butanol and ethylmethanesulfonate. 562 The development of assays for the visual detection and quantification of alkylating agents is important because these compounds are potentially genotoxic impurities that may be present in pharmaceuticals. The rationale here is based on the fact that the alkylation of 1 occurs on the phenolate moiety, and the ether generated is colorless, as shown previously by Linert et al 563 in a kinetic study of the methylation of a series of pyridinium-N-phenolate betaine dyes in organic solvents.…”
Section: Chromogenic Chemosensors For Neutral Analytesmentioning
confidence: 99%
“…Sensor technologies have been an active area of research for a great many years with examples of the oxygen monitoring electrode for surgery and first-, second- and third-generation glucose biosensors finding widespread adoption and now routine use [1]. Sensor technologies have enabled environmental monitoring [2], improved control of industrial processes [3], given rise to purer drug formulations [4,5] and found numerous medical and biological applications, including the measurement of glucose for diabetes [6], lactate for a range of conditions [7] and the routine determination of blood clotting [8]. Sensor technologies have also been used in wild animal research since the first application of an intravascular pO 2 electrode in a diving penguin in 2005 [9], but the field of wild animal sensing lags far behind the biomedical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods that use these techniques for detecting 4-chloro-1-butanol at the sub-ppm level in APIs have been reported. 11,17,18 In a previous study, we developed a GC-MS method for 4-chloro-1-butanol analysis.…”
Section: Introductionmentioning
confidence: 99%